Etude comparative de la composition floristique et de la structure des forêts à Scorodophloeus zenkeri (Harms) de Yangambi et Yoko en Province de la Tshopo, RD Congo - MAINGOLO, LOBELA; BENGWELA MONGOLU; BENGWELA AMUDA; MADEKPE KONGBO; BOHOLA LUFUKARIBU (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The present research aims to compare the diametric and floristic structures of the same forest type to Scorodophloeus zenkeri (Harms) in two different sites (Yangambi Biosphere Reserve and Yoko Forest Reserve). To do this, the full inventory was carried out in six hectares, using longitudinal plots of 100 m and crosswise of 100 m. Each plot of 1 ha (100 m side) wassubdivided into for small plots of 50m x 50m (0.25 ha). The ends of the plots are pegged to verify the tree’s membership in the plot during the count. In these plots, we counted and measured the circumference (at 1.30 m from the ground) of all trees at dhp ≥ 10 cm, which allowed us to collect structural and floristic data for this study. The results obtained are as follows: the density (402 ± 35.79 and 440 ± 26.51 individuals per hectare) and the basal area (34.92 ± 3.75 and 34.26 ± 2.5 m². ha-1) recorded respectively in Yangambi and Yoko do not indicate differences between the two sites. The analysis of the diametric structures shows a decreasing distribution of the number of individuals with the increase of the diameter of the trees. The forest stands of Yangambi and Yoko are barely a single floristic group from the point of view of floristic similarity.